An Analysis of the Effects of Age, Education, and Marital Status on Female Labor Force Participation in East Java 2020-2022 Period - Septania, Pearlsy Angelina; Ashar, Khusnul (Journal of Development Economic and Social Studies, 2026)
Female labor force participation in East Java Province exhibits fluctuating trends, despite the female population outnumbering the male population. This phenomenon is presumed to be influenced by individual characteristics, particularly age, educational attainment, and marital status. This study aims to examine the effects of age, education, and marital status on female labor force participation in East Java during the 2020–2022 period. A quantitative approach is employed using secondary data obtained from publications of Statistics Indonesia (BPS) East Java. The analysis applies panel data regression, with model selection conducted through the Chow test, Hausman test, and Lagrange Multiplier test, alongside classical assumption tests to ensure model validity. The results indicate that age and education have a positive and significant effect on female labor force participation, while marital status has a significant negative effect. These findings highlight the importance of expanding access to education and implementing gender-equitable policies to enhance women’s participation in the labor market.